BIODIVERSITY OF THE MICROFLORA OF THE SALT LAKES DZHAKSY-KLYCH AND BUGA-DZHAILY - Issayeva Akmaral Umurbekovna,; Leska Boguslawa,; Uspabaeva Aigul Amankulovna,; ymkent; Tleukeeva Assel Yerzhanovna,; Abubakirova Azhar, (Academic Journal of Physical and Chemical Sciences, 2020)
The article illustrates the results of microbiological and chemical studies of samples of salt lakes in the south of Kazakhstan, such as Dzhaksy-Klych and Buga-Dzhaily. It was found that the samples from the bottom of the dried up Small Aral Sea are dominated by ions of magnesium, potassium, calcium, iron and copper. Moreover, the presence of pesticides was revealed: acetamiprid, fenhexamide, folpet-like compounds, tetrahydrophtolamide, which are used in the agro-industry. Samples of Lake Dzhaksy-Klych were isolated from different layers of halite, magnesium, and sulfate salts. Salt-containing raw material of Lake Buga-Dzhaily contains 96.0 ± 8.9 wt.% NaCL, the content of magnesium ions ranges from 0.17 ± 0.01 -4.01 ± 0.0 wt.%, The presence of sulfur is within 0,26 ± 0.02%. 1.71 ± 0.12 wt%. The amount of heavy metals is below the permissible concentration. It was found that the increased content of magnesium in the samples proves the presence of mixed sodium-magnesium layers. he number of heterotrophic microorganisms in the samples of salt lakes is approximately 103-104 CFU/g, enterobacteria -103 CFU / g, micromycetes in the amount of (6.0 ± 0.5) x 103 CFU/g g were found only in the sample of sulfate salts and silt sampled at a distance of 1.0 m from the coastline. The distribution and density of microflora on the coastline indicate an increased anthropogenic factor due to salt extraction.